PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1942)
Abstract The article presents some problems that were presented by the Board of Examiners of the American Institute of Accountants as the second half of the May, 1942 Certified Public Accountants Examination in accounting theory and practice. In one of the question, examinees were asked to prepare a columnar work sheet summarizing the foregoing data in rational manner and form. They were also asked to prepare a concise statement showing the realization of assets, liquidation of liabilities and operations during the receivership; also unsecured creditors' claims and available assets on November 20, 1941. In another question a transcript of "Insurance account" and "note" covering unrecorded liability was given for the period starting from July 2, 1940 and ending December 31, 1941 and examinees were asked to prepare a columnar analysis showing proper distribution of debits and credits. They were also asked to prepare there from the entries that will adjust surplus, profit and loss and other December 31, 1941, balance-sheet headings involved.